2005
DOI: 10.1016/j.orthres.2004.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Rapid phenotypic changes in passaged articular chondrocyte subpopulations

Abstract: Articular chondrocytes are often expanded in vitro and then used to assist in healing articular cartilage defects. We investigated the extent of dedifferentiation in monolayer-passaged, zonal articular chondrocytes by using quantitative, real-time PCR. The relative gene expressions for collagen type I and 11, aggrecan, and superficial zone protein were analyzed for relevant passage numbers (PO-P4) to determine how the expansion of chondrocytes affects the expression of cartilage extracellular matrix proteins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
457
4
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 569 publications
(501 citation statements)
references
References 30 publications
24
457
4
4
Order By: Relevance
“…14,18 Expression levels greater than two standard deviations from the mean were considered outliers and removed, since the removal of outlier results in less standard deviation with less effect to the means. The means and standard deviations were then calculated by Excel spreadsheet software (Microsoft, U.S.).…”
Section: Data Normalization and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…14,18 Expression levels greater than two standard deviations from the mean were considered outliers and removed, since the removal of outlier results in less standard deviation with less effect to the means. The means and standard deviations were then calculated by Excel spreadsheet software (Microsoft, U.S.).…”
Section: Data Normalization and Statistical Analysismentioning
confidence: 99%
“…6,8 While the exact mechanism of this process is poorly understood, a recent study by Darling and Athanasiou using goat chondrocytes has suggested that this shift in gene expression is initiated in the early stages of in vitro cultivation. 14 Furthermore, another variable in this process is the status of differentiation in osteoarthritic (OA) chondrocytes. As chondrocyte expression in known to undergo change with the degeneration of articular cartilage, the impact of osteoarthritis in donor cartilage on ACI is also poorly researched in the literature.…”
mentioning
confidence: 99%
“…1F). Based on the state of the art on the redifferentiation capacity of culture-expanded chondrocytes from a variety of species, including goats, 27 we would expect that expression of collagen type I persisted in all pellets.…”
Section: Postexpansion Chondrogenic Capacity Of Goat Chondrocytes In mentioning
confidence: 99%
“…3 In addition, during ex vivo expansion chondrocytes rapidly lose their chondrogenic state (dedifferentiation) and express a fibroblastic phenotype with decreased expression of chondrocyte proteins, such as aggrecan and type II collagen, and an increase in the production of fibroblast proteins, namely collagen type I. 4,5 The use of microcarriers for chondrocyte expansion has been investigated to overcome some of these effects. [6][7][8][9][10] Microcarrier culture offers a cost-efficient method of propagating large populations of cells due to a high surface area to volume ratio.…”
mentioning
confidence: 99%